The development of cadastral database selection application to support modern cadastral and Malaysia spatial data infrastructure - Omar, Abdullah Hisam (Universiti Teknologi Malaysia, 2007)
The development of State Digital Cadastral Database (SDCDB) by Department of Survey and Mapping Malaysia (DSMM) is one of the initiatives to shift towards modern cadastral system. Coordinated Cadastral System (CCS) is one of the modern cadastral elements. One of the conceivable benefits of introducing CCS is the facilitating of work performed in the digital environment. The introduction of CCS partly comes from the need to support the digital cadastral database and its uses. Cadastral data need to be adjusted in order to verify the network closure. The functions of the data selection are; i) to generate zones and overlapping areas automatically, ii) to prepare input data files for a particular zone, iii) to extract cadastral information from existing SDCDB, and iv) reformatting existing data as a input file into least squares adjustment software. In order to support the adjustment process, data selection application will filter out the hanging lines respectively to the selected cadastral lots. Those steps are to ensure that cadastral lots are kept in the closed polygons, which is important in the adjustment process. A large number of cadastral information in the land records can be extracted more efficient digitally compare to a conventional approach. The success of the development of National Digital Cadastral Database is depends on the efficiency of the Automated Data Base application. The Cadastral Database Application has been tested and functioning effectively.